Differences in tissue-associated bacteria between metastatic and non-metastatic colorectal cancer - Zhou, Peng; Dai, Ze; Xie, Yaoyao; Li, Tong; Xu, Zhizheng; Huang, Yanhong; Sun, Desen; Zhou, Yuping (Frontiers in Microbiology, 2023)
Background and aims Accumulated evidence indicates that the intestinal microbiota plays crucial roles in the initiation and progression of colorectal cancer (CRC). However, the effects of the tissue-associated microbiota on CRC metastasis are poorly defined. The aim of this study was to explore the differences in bacteria between metastatic and non-metastatic CRC tissues and identify potential bacterial species that associate with CRC metastasis. Methods 16S rDNA amplicon high-throughput sequencing was used to test the intestinal tissue-associated microbiota in patients with metastatic CRC (n = 48) and non-metastatic CRC (n = 44). The microbial diversity and differential species were analysed by standard microbiological methods, and then the differential bacteria were confirmed by qPCR. Receiver operating characteristic (ROC) curves were plotted to evaluate the ability of the differential bacteria in predicting the metastasis of CRC. In addition, the microbial compositions of tumor-adjacent tissues from the metastatic and non-metastatic CRC groups were analysed. Results The α- or β-diversity of microbial community between the metastatic and non-metastatic CRC groups did not exhibit significant differences. However, some bacterial abundances between two groups showed significant differences. At the phylum level, Bacteroidota and Desulfobacterota were significantly higher in the metastatic group than in the non-metastatic group, while Proteobacteria was significantly decreased in the metastatic group. At the genus level, Bacteroides (mainly composed of Bacteroides fragilis and Bacteroides uniformis) was significantly higher in the metastatic group than in the non-metastatic group, while Streptococcus and Escherichia-Shigella were significantly decreased. The ROC curves of the selected bacteria showed area under the curve (AUC) values ranging from 0.598 to 0.69; when CEA and the selected bacteria were combined, the AUC values increased from 0.678 to 0.705. In addition, the bacterial composition of tumor-adjacent tissues from the metastatic and non-metastatic CRC groups were also different, and the differential bacteria were consistent with those between metastatic and non-metastatic CRC tumor tissues. Conclusion The bacterial composition of tumor and tumor adjacent tissue from the metastatic CRC group was different from that of the non-metastatic CRC group; in particular, Bacteroides was increased, and Streptococcus was decreased. These findings are helpful to further reveal the mechanism of CRC metastasis and provide new ideas for the clinical diagnosis and treatment of CRC metastasis.